The image of a preschool child in socialist Hungary - Zsófia, Nemes-Wéber, Zsófia (Acta Cultura et Paedagogicae, 2026)
When examining the image of children, it must be kept in mind that there are two types of images of children in every era. One is the real child image, which is a knowledge construction based on the individual values of adults in the real world. The other is the ideal child image, which is the image of a child that is expected by society and proclaimed to be perfect. (Nóbik, 2000) The image of the ideal Soviet child, of a child with a strong collective spirit, fosters friendship with children of other nationalities, and last but not least, nurtures a strong love for the socialist homeland. The child can reach the goal and fit into society through education. The basis of their approach is the ideal they want to transform the child into. (Pukánszky, 2003) The miniaturized communist warrior child was therefore the goal of education during the period of socialism. (Kéri, 2003) The kindergarten became the primary scene of conscious education influenced by politics, and the kindergarten teacher became the mediator of the principles. A phenomenon typical of the era is the large-scale development of institutional provision, as a result of which in 1958 only 29% of children of preschool age attended kindergarten, while in 1972 it was already 62%. (Kurucz, 1970 és Kökény, 1983) The pedagogical environment has therefore changed significantly compared to the past. The ideology of all the nations of the socialist bloc was permeated by the theories of Soviet thinkers, norm and performance orientation, individual values and self-realization were replaced by the idea of conformism and collectivism. (Pálfi & Vargáné, 2023) My research covers the examination of the ideal of the preschool child, the transformation of images of children published in the journal Óvodai Nevelés, the regulations of preschool activities and the principles of education.